Evaluation of clinical pharmacy services within the primary care–mental health integration model at the Tuscaloosa Veterans Affairs Medical Center - Parikh, Mamta (Ment Health Clin, 2016)
INTRODUCTION: The purpose of this review is to evaluate the direct delivery of health care to veterans before and after incorporating clinical pharmacy services within primary care mental health integration (PCMHI) at the Tuscaloosa Veterans Affairs Medical Center. Prior to establishing the role of the clinical pharmacy specialist (CPS) within PCMHI, the primary care providers deferred all mental health assessments to specialty mental health. As the demands of the service grew exponentially, assistance from clinical pharmacy was critical. METHODS: A randomized, computer-generated list of 114 patients selected for the retrospective chart review was used to evaluate clinical outcomes in patients enrolled in the PCMHI clinic 1 year preincorporation and postincorporation of CPS. Outcome measures included the number of patients discharged from the PCMHI clinic upon achieving therapeutic goals or discharged to specialty mental health due to therapeutic failure or adverse drug events with first- and second-line psychotropic agents. RESULTS: When contrasting the end points, there was a 60% increase in the number of patients who achieved therapeutic goal and a 32% decrease in the number of patients discharged to specialty mental health clinic postincorporation of CPS into PCMHI as compared to preincorporation of CPS (P = .024). DISCUSSION: The results support the significance of CPS in the PCMHI in providing pharmacotherapy, patient education, and medication monitoring for managing psychiatric conditions, such as depression, anxiety, and insomnia. In addition, patients had greater accessibility to medication and frequent monitoring and follow-up, ultimately improving patient outcomes.